The Prometheus Bomb : The Manhattan Project and Government in the Dark - Sullivan, Neil J., 1948- (Book collections on Project MUSE., 2016)
"During World War II, the lives of millions of Americans lay precariously in the hands of a few brilliant scientists who raced to develop the first weapon of mass destruction. Elected officials gave the scientists free rein in the Manhattan Project without understanding the complexities and dangers involved in splitting the atom. The Manhattan Project was the first example of a new type of choice for congressmen, presidents, and other government officials: life and death on a national scale. From that moment, our government began fashioning public policy for issues of scientific development, discoveries, and inventions that could secure or threaten our existence and our future. But those same men and women had no training in such fields, did not understand the ramifications of the research, and relied on incomplete information to form potentially life-changing decisions. Through the story of the Manhattan Project, Neil J. Sullivan asks by what criteria the people in charge at the time made such critical decisions. He also ponders how similar judgments are reached today with similar incomprehension from those at the top as our society dives down the potential rabbit hole of bioengineering, nanotechnology, and scientific developments yet to come"--